Identification of Free Radical in Main Stream Cigarette Smoke in Cigarette with Clove mix (Kretek) and Cigarette without Clove mix (White) - Anggarani, Ni Kadek Nova; Djoko H.S., D.J.; Juswono, Unggul P. (BULETIN FISIKA, 2020)
Cigarette smoke is a source of free radicals. Cigarette smoke is a component of Aerosols and free gases that contain large amounts of chemical compounds. Cigarette smoke can be divided into two: main smoke and side smoke. The main smoke of cigarettes inhaled by smokers is known to cause a buildup of harmful substances and causes of oxidative stress so that research is carried out using ESR Leybold Heraeus. The sample used is a smoke sample from two types of cigarettes that are popular in Indonesia. The measurement is done by pulling smoke directly into the measurement tube. Then the resonance pattern is observed and the external magnetic field is calculated and the value of the lande factor is based on frequency and current data. Measurements result showed resonance in both types of cigarettes, at a frequency of 32.4-70.8 MHz and obtained values of lande factors that vary and have a value between 1.9-2.1 with two acquisition values that are outside the range that is 1.8368; and 2.2060. There are differences in the number of resonances that occur for each sample. This difference can be due to differences in the constituent of content and the texture of cigarettes which can affect the results of the combustion process .